"Creación de una microempresa de servicio de cafetería en el "Hospital Un Canto a la Vida" con la inclusión de las madres de niños y jóvenes con capacidades diferentes en el Sur de la Ciudad de Quito". - Velástegui Varela, Regina Jacqueline (2010)
The project aims to reduce poverty and unemployment through the creation of small businesses run by mothers of children and youth with skills especiales.El cafeteria will be located within the premises of the Hospital a Song to Life, the site predisposed for operation in which the marketing of products will be light, such as breakfast, soft drinks, snacks, which can satisfy the appetite of consumers and offer high quality standards in production and distribution.